Comparison of Misleading Information on Sriwijaya Air SJ-182 Accident between @detikcom and @kompascom - Binti Qumairoh; Zainal Abidin Achmad; Ririn Puspita Tutiasri; Kusnarto Kusnarto (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
Misleading information often appears in political events. But the impact is different if it happens in the event of an accident. This study describes the form of misleading information that occurred in the Sriwijaya Air SJ-182 plane crash in the Kepulauan Seribu, by comparing the information content on Instagram account of @detikcom and @kompascom. This study uses a qualitative research method with a netnography approach, to explore the comparison of misleading information on the two accounts that have high credibility as news media in Indonesia. Netnography provides the ability to reveal and track various interactions of netizens with news on Instagram about the Sriwijaya Air SJ-182 accident. The number of informants in this study amounted to six people with the following criteria: (1) commenting on the @detikcom and @kompascom about the news of the Sriwijaya Air SJ-182 crash, (2) having knowledge aboout the rules and ethics of journalism. This study compares misleading information in the data on the number of victims, technical diction, credibility of news sources, and illustration support. The results of the study concluded that @detikcom caused more misleading information than @kompascom. The @detikcom account is less detail in conveying data, uses technical diction without adequate explanation, careless in displaying quotes from news sources, and lacks accuracy.